Helicobacter pyloricagA 12‐bp insertion can be a marker for duodenal ulcer in Okinawa, Japan. Issue 2 (22nd January 2013) - Matsuo, Yuichi; Shiota, Seiji; Matsunari, Osamu; Suzuki, Rumiko; Watada, Masahide; Binh, Tran Thanh; Kinjo, Nagisa; Kinjo, Fukunori; Yamaoka, Yoshio
Abstract Background and Aim Helicobacter pylori cagA can be classified into mainly two types (East‐Asian‐type and Western‐type cagA) according to the repeat regions located in the 3′ region. Recent studies showed that the Western‐type cagA in strains from Okinawa, Japan formed a different cluster (J‐Western‐type cagA subtype). It has also been reported that J‐Western‐type cagA possesses a 12‐bp insertion located in the 5′ region of cagA sequence. Methods The prevalence of 12‐bp insertion in cagA in Okinawa and the United States (U.S.) was examined by DNA sequencing. The primer pair that can detect the 12‐bp insertion only by polymerase chain reaction was then designed. The prevalence of strains with 12‐bp insertion was examined in 336 strains isolated from Okinawa by polymerase chain reaction. Results In case of Western‐type cagA/vacA s1m2 strains, the prevalence of 12‐bp insertion was significantly higher in strains isolated from Okinawa than that from the U.S. (P = 0.002). Phylogenetic tree showed that strains with 12‐bp insertion formed two individual clusters within J‐Western‐type cagA subtype; one is from Okinawa and another is from the U.S. The designed primer set showed high sensitivity (100%) and specificity (90.8%) in Okinawa. The 12‐bp insertion was found in 23.7%, 14.3%, 4.2%, and 4.0% of strains with duodenal ulcer (DU), gastritis, gastric cancer, and gastric ulcer (GU), respectively (P < 0.001 for DU vs GU) in Okinawa. Conclusions Although the mechanisms are unknown, the presence of 12‐bp insertion was associated with the presence of DU and might have a suppressive action on GU and gastric cancer.